The Line that Divides us: - Amanda Cunha (Revista Brasileira de Estudos da Presença)
A common factor among white people is the denial that they are racialized subjects, so that they use white fragility and innocence as strategies to protect and enjoy privilege and racial superiority. By the other hand, decolonial art is made up of a set of works that aim to separate the artistic production of non-Europeans and non-whites from a supposed position of inferiority based on coloniality. Thus, this research sought to understand how black theater, understood from this decolonial perspective, provides white Brazilian and Portuguese spectators with a racializing experience. The results allowed us to explore shared understandings about white identity, contributing to understanding the process of racialization of white spectators.